Fabrication of flourine doped tin oxide with different volume of solvents on FTO seed layer by hydrothermal method - M.L. Mohd Napi,; N. Nayan,; M.K. Ahmad,; F.I.M. Fazlee,; N.K.A. Hamed,; N.S. Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Flourine doped tin oxide films were synthesized by using hydrothermal method with different volume of solvents. The thin film growth was carried out by fixing the concentration of tin and fluorine element precursors by only varying their solvents which were 2-propanol and DI water. The fabrication of FTO thin film by using mineral salt group as tin precursor with hydrothermal method on soda lime glass showed that the nanostructured growth did not distribute largely and took longer time. The seed layer of FTO has been used to overcome these problems thus the thin film growth distributed largely in short time. These experiments were conducted at a constant of hydrothermal temperature and reaction time which were 150°C and 5 h respectively. The result showed that, there was a change on the surface morphology in the formation of FTO films. The minimum value of sheet resistance was 0.1475 Ω/sq which was obtained using 65 mL of 2-propanol and 20 mL of DI water was lower than sheet resistance of commercial FTO films of 01693 Ω/sq. This fabricated FTO films showed a good transparency with higher of transmittance than 80%. The experimental findings suggested that 65 mL amount of 2-propanol and 20 mL of DI water in precursor solutions could produce the better of FTO performance than commercial FTO.